Selective mechanization-A way forward in augmenting the productivity and profitability of safflower (Carthamus tinctorius L.): Selective mechanization-A way forward in augmenting the productivity and profitability of safflower (Carthamus tinctorius L.) - C SUDHAKAR; C SUDHA RANI (Journal of Oilseeds Research, 2020)
An experiment was taken up to study the influence of mechanization of critical tasks like sowing, inter cultivation harvesting and shelling on throughput and economics of safflower cultivation under medium black soil and under both conservative and mechanized methods. Results indicated that the performance of Safflower in selective mechanization plot registered significantly higher growth and yield attributing characters resulting in significantly higher seed yield (1333 kg/ha), net returns (`33539/ha) and B:C ratio (4.01). Selective mechanization produced nearly 14.7% higher seed yield over traditional cultivation (normal plot). Higher energy output (20764 MJ/ha), net energy returns (15423 MJ/ha) and energy use efficiency (3.89) as compared to traditional normal pot (17713 MJ/h; 10220; 2.36). Selective mechanization helped to save 121.25 hrs time period and 80 labour and thus reduced the cost of cultivation by ` 4417/ha and increased the net returns by `14355/ha as compared to normal (traditional) plot.